2018
DOI: 10.3390/v10090460
|View full text |Cite
|
Sign up to set email alerts
|

Classical Swine Fever Virus p7 Protein Interacts with Host Protein CAMLG and Regulates Calcium Permeability at the Endoplasmic Reticulum

Abstract: We have previously shown that Classical Swine Fever Virus (CSFV) p7 is an essential nonstructural protein with a viroporin activity, a critical function in the progression of virus infection. We also identified p7 domains and amino acid residues critical for pore formation. Here, we describe how p7 specifically interacts with host protein CAMLG, an integral ER transmembrane protein involved in intracellular calcium release regulation and signal response generation. Detection of interaction as well as the ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Previously, we have studied the interaction of host proteins with several CSFV proteins. We have shown that the structural CSFV core protein interacts with host SUMO1, IQGAP1, UBC9 and OS9 [12][13][14][15]; shown that p7, a viroporin, interacts with CAMLG [28]; and more recently, described the interaction of the major structural glycoprotein E2 with PPP1CB and DCNT6 [21,22]. Importantly, besides affecting virus replication, some of these host-virus protein interactions play a role in determining virus virulence in swine [12][13][14]22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have studied the interaction of host proteins with several CSFV proteins. We have shown that the structural CSFV core protein interacts with host SUMO1, IQGAP1, UBC9 and OS9 [12][13][14][15]; shown that p7, a viroporin, interacts with CAMLG [28]; and more recently, described the interaction of the major structural glycoprotein E2 with PPP1CB and DCNT6 [21,22]. Importantly, besides affecting virus replication, some of these host-virus protein interactions play a role in determining virus virulence in swine [12][13][14]22].…”
Section: Discussionmentioning
confidence: 99%
“…The development of mutant viruses containing residue substitutions disrupting interactions between a virus protein and its host cell partner constitutes a useful tool to analyze the potential role of a particular E2-host protein interaction in several virus functions [12][13][14]27]. We have previously reported that the E2-SERTAD1 interaction appears to be conformation-dependent since alanine scan mutagenesis failed to map E2 residues critical for mediating interaction [23], an approach successfully used by us to map residues within the foot and mouth disease virus (FMDV) and CSFV proteins interacting with host protein ligands [14,[27][28][29][30]. E2 amino acids mediating the interaction with SERTAD1 were mapped using the yeast two-hybrid methodology as described in our previous study [22].…”
Section: Identification Of Csfv E2 Residues Critical For Sertad1 Intementioning
confidence: 99%
“…GFP-MGF360-16R was inserted into pTagGFP-N1 where GFP-MGF360-16R is under the control of the CMV promoter, and RFP-SERTAD3 and RFP-SDCBP were cloned into pTagRFP-N; both plasmids were constructed by Epoch Life Sciences. Cell fixation and imaging was done as previously described [24].…”
Section: Colocalization Studiesmentioning
confidence: 99%
“…Through mechanisms mediated by interaction between virus and host proteins, the virus could modulate the host cell response, permitting the virus to manipulate host metabolic pathways to facilitate its replication. In that regard, we have already reported that structural CSFV Core protein interacts with host SUMO1, IQGAP1, UBC9 and OS9 [11][12][13][14]; the interaction of nonstructural protein p7, a viroporin, with CAMLG [28]; recently, we characterized the interaction of major structural glycoprotein E2 with host proteins PPP1CB and DCNT6 [20,21]. Interestingly, some of these host-virus protein-protein interactions also play a role determining virus virulence in swine [11][12][13]21].…”
Section: Discussionmentioning
confidence: 92%
“…These mutant viruses, containing residue substitutions disrupting interactions between a virus protein and its host cell partner, have been used to analyze the potential role of a virus protein and host protein interaction in several virus functions. We have successfully used this approach to discover specific residues within foot and mouth disease virus (FMDV) and CSFV proteins interacting with host protein ligands [13,[27][28][29][30].…”
Section: Identification Of Csfv E2 Residues Critical For Ccdc115 Intementioning
confidence: 99%